2018
DOI: 10.1080/09537104.2018.1478400
|View full text |Cite
|
Sign up to set email alerts
|

The use of platelet-rich plasma (PRP) to improve structural impairment of rat testis induced by busulfan

Abstract: Platelet-rich plasma (PRP) has a potential effect on tissue repair through proliferation and differentiation of tissue progenitor cells. The aim of this study was to evaluate the effect of PRP on the testis structure and function in infertile rat model by stereological method. Thirty-two male rats were divided into four groups. Infertility was induced by the administration of busulfan (BUS) (10mg/kg, I.P., single dose). PRP (80μl, testis local injected, single dose) was administered for the subjects. After 48 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(53 citation statements)
references
References 26 publications
0
37
2
1
Order By: Relevance
“…A current focus of research is the effect of busulfan on testes and semen quality. [6][7][8][9][10][11][12][13][14][15][16] In our study, however, no effect on the male and female reproductive organs was observed in the busulfan-treated animals. This may be due to the fact that studies investigating the effect of busulfan on reproductive organs either administer high dosages like 10 to 20 mg/kg/bw busulfan intraperitoneally or rely on prolonged administration of oral dosages of busulfan for 2 weeks or more.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…A current focus of research is the effect of busulfan on testes and semen quality. [6][7][8][9][10][11][12][13][14][15][16] In our study, however, no effect on the male and female reproductive organs was observed in the busulfan-treated animals. This may be due to the fact that studies investigating the effect of busulfan on reproductive organs either administer high dosages like 10 to 20 mg/kg/bw busulfan intraperitoneally or rely on prolonged administration of oral dosages of busulfan for 2 weeks or more.…”
Section: Discussionmentioning
confidence: 60%
“…This may be due to the fact that studies investigating the effect of busulfan on reproductive organs either administer high dosages like 10 to 20 mg/kg/bw busulfan intraperitoneally or rely on prolonged administration of oral dosages of busulfan for 2 weeks or more. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] Even though busulfan is known to cause sterility, 5 these effects may therefore not be present in rat studies not administering high dosages of busulfan. No effect on reproductive organs was observed in animals receiving busulfan impurity 5 at dosages 10 times higher than the busulfan dose administered in this study.…”
Section: Discussionmentioning
confidence: 99%
“…In this experimental study, the authors showed beneficial effects of PRP on I/R induced oxidative stress, histological structure of testicles, and hormone production. In another experimental study by Dehghani et al, 12 a positive effect of intra‐testicular PRP injection was observed on total testosterone levels in rats with testicular atrophy induced by busulfan. In our study, we showed that the mean total testosterone levels were statistically significantly higher in the I/R + PRP group and the mean LH levels were significantly lower than the I/R + Saline group ( P = .001).…”
Section: Discussionmentioning
confidence: 86%
“…We believe that PRP may contribute positively to spermatogenesis, as it contains many growth factors. It has been also previously shown that PRP increases spermatogonia, primary spermatocyte counts, and sperm motility 12 . Growth factors balance between the germinal cell proliferation and differentiation 32 .…”
Section: Discussionmentioning
confidence: 89%
“…• Subgroup 1-B: Subjected to intratesticular PRP injection into the left testis parenchyma 10µl (2000 x 109/L) single dose [12] .…”
Section: Methodsmentioning
confidence: 99%